Fundamentals of Digital Image Processing and Basic Concept of Classification - Shawal, Shammi; Shoyab, Muhammad; Begum, Suraiya (International Journal of Chemical and Process Engineering Research, 2014)
We have to classify and analyze digital images for different study and purposes. Digital images are obtained from sources like camera, satellites, aircraft etc. Data obtained from satellites or aircraft i.e, the space based and remote sensing data needs to be corrected as they are usually geometrically distorted due to their acquisition system and the movements of the platform of aircraft. Processing and pre-processing are necessary for such correction prior to image classification. Image Processing is a technique which is used to enhance raw images received from cameras, satellites, space probes, aircrafts etc. and Digital image processing is the technique of processing images in the form of discrete digital brightness using digital circuits or digital computers. Image analysis and classification starts when processing and pre-processing ends.